The New Library of the University of Aveiro - Lemos, Laura Oliva Correia (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The new library of the University of Aveiro was inaugurated in 1995. The architect selected to put the new library project into practice was Álvaro Siza, an internationally recognised Portuguese architect. The project was assigned in 1987.